ANALISIS PEMASARAN BAWANG MERAH VARIETAS LEMBAH PALU DI DESA SOULOVE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Ika, Ika; Amtiran, Ross M. Olva; Hadayani, Hadayani (AGROTEKBIS, 2018)
The research aimed to find out the marketing channel of Palu valley onion varieties, the amount of marketing margin obtained by each marketing institution of Palu Valley onion varieties, the amount of price received by the farmer (producer) in each marketing channel of Palu Valley onion varieties, and know the marketing efficiency of Palu Valley onion varieties. The researcher took 29 respondents from 85 farmers using simple random sampling method. Moreover, the researcher used tracing Sampling Method for 5 merchants to determine the merchant respondents, the determination of consumer respondents had been done purposively (Purposive) for 5 people so that the number of respondents in this research were totally 39 respondents. Data analysis used was marketing analysis. The results showed that there were two channels of marketing commodity of onion varieties of Palu valley located in Soulove Village which are: first channel, farmer → collector → retailer → consumer. The second channel, farmers → collectors → consumer .The marketing margin of Palu Valley onion varieties obtained for the first channel was IDR 25,000, and marketing margin of Palu valley onion varieties obtained for second channel was IDR 15.000. The price obtained by farmers in the first channel was 61.53%, and the second channel was 72.72%. The value of first channel marketing efficiency was 1.00% and for the second channel was 1.18%.